Konsep Komunikasi terhadap Remaja dalam Keluarga Islam menurut Pandangan Al-Qur’an - Rifiana (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
This article entitled "The Concept of Communication in Islamic Families and Its affect for Teenagers" purpose it’s to find out how the ethics of communicating between parents and children were applied by Prophet Ibrahim and Luqman to their children as an example for parents in establishing communication with their children. In this study, the author uses library research by collecting primary written data such as from the Al-Quran related to communication problems, as well as secondary sources such as Islamic family communication books. The effective concept of communication in the family is to prioritize good language, avoid harsh words and high voices and prioritize courtesy and ethics when communicating with both older and younger people. Therefore, parents and teenagers can communicate with ethics exemplified in the Qur'an. Good communication between parents and children will have an impact on growth and development, especially for teenagers, so will be able to make more harmonious relationship between families.